UW-River Falls vision and values survey: Fall 2005 - Trechter, David; Parks, Denise; Hadley, Shelly (My University, 2005)
Conducted during the Fall of 2005, this on-line survey sought opinions in seven areas. Respondents were asked to describe the campus, offer what its core values should be in the 21st century, and describe their vision for the institution. In addition, respondents could offer an opinion on UW-RF's strengths, suggest its future defining characteristics, offer what changes would be needed to accomplish those characteristics, and weigh in on how Chancellor Don Betz should be spending his time. The UW-RF Vision and Values Survey produced almost 10,000 discrete comments from nearly 600 students, faculty, staff, and community members.
42 p.
Keywords: University of Wisconsin-River Falls; University of Wisconsin-River Falls--Employees; Vision and values survey; Core visions and values; Universities and colleges--Wisconsin--River Falls; Universities and colleges--Wisconsin--River Falls--Administration; Educational leadership--Wisconsin--River Falls